Urgensi Implementasi Pendidikan Multikultural di Sekolah - Iis Arifudin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Indonesian nation consist of many kind of culture, ethnic, race, religion, etc. At one side that diversity is a treasure of Indonesian, but at other side it triggers social conflict. Conflict that happens about three decade of New Order power is because our education always teaching similarity (uniformity) and averse plurality. Therefore, this paper suggested multicultural education as solution to this problem. Multicultural education has to be implemented on learning process at school. It not necessarily became separated lesson, but can integrated to every lesson . Multicultural education is a process to cultivating attitude to respect each other, honest, and tolerant to cultural diversity that exit on the plural society. With multicultural education we hope there’s toughness and flexibility of this nation to face the clash of social conflict.